Les enjeux idéologiques et argumentatifs de la formule « same sex marriage » - François Labatut (Glad!)
This article presents a qualitative and computer-assisted, corpus-based analysis of the use of the “same sex marriage” formulae during the Marriage (Same Sex Couples) Act debates in Great Britain in 2013. By drawing on Krieg-Planque’s work (2009), I want to show the reasons why same sex marriage may be assimilated to the discursive notion of formulae. The study of statistically relevant collocational patterns will help to better comprehend the ideological and argumentative dimensions of this expression. Furthermore, systematic comparisons with so-called synonymous expressions such as “gay marriage” and “homosexual marriage” will allow me to detail the socio-linguistic and metalinguistic implications at stake and question the ways cognitive representations of LGBTQ+ couples are shaped in political discourse.